Potential Utilization of Rubber Seed Meal as Feed and Food - Abiola Oluodo, Lukman; Huda, Nurul; Fay Komilus, Connie (International Journal of Engineering and Technology, 2018)
Feed and food crisis has been a global concern due to its increasing prices. It led researchers to consider an alternative non-conventional edible material. This paper discussed the previous studies conducted on rubber seed as feed and food.Â  Rubber Tree (Hevea brasiliensis)Â is a multipurpose tree; grown primarily for the production of latex with numerous useful by-products such as rubber seed, woods and oil. The rubber seed has a promising amount of crude protein, with the existence of a major toxic compound (cyanogenic compound) which has hindered the proper utilisation of the existing nutrient. The present review finds out the nutritional composition of the rubber seed to be moisture content was 3.99%, crude protein 23, crude fat 68.5 and ash 4.3 g/100g respectively. The amino acid in rubber seed was high in Glutamic acid (16.13%) and low in Cysteine (0.78%). Since, rubber seeds contained substantial amount proximate components, therefore it could be assumed as edible food and promising feed resource for livestock. Despite its promising protein contents, rubber seed meal contains cyanogens compound but this drawback could be overcome by boiling and storage time period which could lead to increase the nutrients availability and utilisation of rubber seed as edible feed and food.Â